The Multifaceted Nature of Legal English - Sahakyan, Lilit (Armenian Folia Anglistika, 2014)
It is beyond suspicion that legal English stands as a sublanguage of paramount international importance. The extralinguistic basis of legal English has nowadays been extended embracing conflict of overall international-social, political (both foreign and home) interests. As seen from the title of the work, the primary goal of the present article is to investigate the nature of law English. The article covers a detailed analysis of some pivotal, challenging and highly significant linguistic issues that deal with the multifaceted nature of legal English based on the comprehensive historic review of legal English. Thus, the vital importance of the subject is accounted for by the substantial and decisive role legal English plays in our social life.
Keywords: legal English; law English; sublanguage; key features; precision; vagueness; multifaceted nature